Regional Policy of the EU and Intra-Regional Differences in Development Levels. A Case Study of Lodz Region - Maciej Turala (European Regional Science Association (ERSA), 2006)
The regional policy of the EU attempts at minimising the scale of disparities in the level of socio-economic development of regions. Regional policy is one of the key policies of the EU as shown by the fact that over a third of the Community's budget is spent on it. The main objective of regional policy is to help backward regions to catch up, restructure declining industries, diversify agriculture as well as revitalise cities. Poland, the largest of the new member states is at the same time one of the most lagging behind. The Structural Funds are perceived in Poland as one of the main instruments serving regional development. Since the EU and Poland put a great emphasis on regional policy it seems worthwhile to reflect upon its effectiveness. This article does not aim at analysing the changes in the level of disparities between countries or even regions of the EU – there is sufficient literature dealing with this issue. It needs to be noted however, that there often exist far greater disparities in the level of socio-economic development within regions rather than between them. This results from the concentration of positive effects of regional policy in regional centres. The author aims at presenting a methodology and results of research performed in a Polish region of Lodzkie. It concentrated on measuring the level of socio-economic development in the communes of Lodzkie and the scale of intra-regional disparities. Most available analyses of the effectiveness of regional policy concentrates on measuring the level of disparities between regions, mostly due to the fact that there is insufficient statistical material that would allow such comparisons on a lower level of territorial division. The author proposes a methodology that allows such comparisons for Polish communes. It is then tested on communes of Lodzkie (177 administrative units). The results seem to confirm that the regions are strongly polarised – with most of the socio-economic development concentrated in the centre of the region and a peripheral area around it. This leads to a conclusion that specific actions need to be undertaken in order to fully benefit from regional policy activities.
Keywords: 330